Combined effect of Cu and N on bandgap modification of ZnO film towards effective visible light responsive photocatalytic dye degradation. (September 2020) - Vasanthi, D.S.; Ravichandran, K.; Kavitha, P.; Sriram, S.; Praseetha, P.K.
Abstract: This article focuses on the deposition of ZnO, ZnO:N, ZnO:Cu and ZnO:Cu:N thin films using nebulizer spray technique towards the decomposition of textile dyes through photocatalysis. The observed individual optimum doping concentrations of Cu (0.5 wt %) and N (3 wt %) were chosen for the preparation of co-doped films. As doping partners of ZnO, Cu and N result in better outcome when they are used together as co-dopants rather than used individually. The band gap values were found to be decreased from 3.39 (undoped ZnO) to 3.17, 2.94 and 2.58 after N, Cu and Cu:N doping, respectively as observed from the optical study. The dopant induced band gap modifications estimated for the samples using optical transmittance data are correlated with the enhancement in the photocatalytic dye degrading efficiency. Results obtained from XRD, SEM, optical and XPS studies are correlated suitably with the photocatalysis results. The mechanism behind the enhancement of degrading efficiency has been discussed in this paper with the support of structural, compositional, optical and surface morphological analyses. Graphical abstract: Image 1 Highlights: Preparation of visible light active semiconductor photocatalyst using a low cost technique. Effective tuning of band gap of ZnO by Cu:N co-doping. First report on spray deposited ZnO:Cu:N thin films.